Numerical Simulation of a Thermal-Hydraulic-Chemical Multiphase Flow Model for CO2 Sequestration in Saline Aquifers - Ahusborde, Etienne; Amaziane, Brahim; Croccolo, Fabrizio; Pillardou, Nicolas (Mathematical geosciences, 2023)
We consider a reactive multiphase multicomponent Darcy flow in a porous medium while taking into account the effects of temperature. This flow model is coupled to an energy balance equation and ordinary and/or algebraic differential equations to model the chemical reactions. The model is discretized using a cell-centered finite volume method with implicit Euler or second order backward differential formula time discretization. Both sequential and fully coupled fully implicit strategies are considered. Two new DuMu X modules are developed based on the above schemes. Two numerical examples are presented to validate the implementation of the two methods and the capability of the code to solve CO 2 sequestration scenarios. The first test addresses a one-dimensional radial problem to study thermal effects on injectivity during CO 2 storage. For this purpose, isothermal/nonisothermal comparisons are carried out to highlight these differences, which can modify the flow. The second test is chosen to test the code to approximate solutions for a three-dimensional benchmark based on the Johansen CO 2 storage operation. Then, we compare the efficiency, performance in terms of computation time, and parallel scalability of the sequential and implicit methods. In conclusion, both modules demonstrate accuracy, numerical robustness, and the potential to solve realistic problems. With an equal time step, the sequential scheme can be faster than the implicit scheme, but the splitting can present a loss of accuracy, particularly concerning the conservation of mass of the injected CO 2 .